2003
DOI: 10.1097/01.wcb.0000075010.31477.1e
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Visual Cortical Maps after Focal Ischemic Lesions

Abstract: Summary: Plasticity after central lesions may result in the reorganization of cortical representations of the sensory input. Visual cortex reorganization has been extensively studied after peripheral (retinal) lesions, but focal cortical lesions have received less attention. In this study, we investigated the organization of retinotopic and orientation preference maps at different time points after a focal ischemic lesion in the primary visual cortex (V1). We induced a focal photochemical lesion in V1 of kitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…Comparison with previous studies of plasticity after stroke In patients (Rossini et al, 2007) and animal stroke models (Abo et al, 2001;Dijkhuizen et al, 2001Dijkhuizen et al, , 2003Wei et al, 2001;Zepeda et al, 2003Zepeda et al, , 2004, ipsilesional regional reorganization as observed here is correlated with improved behavioral recovery. In rats with small infarcts, activity within the stroke-affected cortex was required for reaching task performance (Biernaskie et al, 2005).…”
Section: Discussionmentioning
confidence: 69%
“…Comparison with previous studies of plasticity after stroke In patients (Rossini et al, 2007) and animal stroke models (Abo et al, 2001;Dijkhuizen et al, 2001Dijkhuizen et al, , 2003Wei et al, 2001;Zepeda et al, 2003Zepeda et al, , 2004, ipsilesional regional reorganization as observed here is correlated with improved behavioral recovery. In rats with small infarcts, activity within the stroke-affected cortex was required for reaching task performance (Biernaskie et al, 2005).…”
Section: Discussionmentioning
confidence: 69%
“…Smaller, shortterm changes (2 d after the lesion) have been reported as well (24). As expected, reorganization is more extensive in young animals (23,25) compared with adults (26). A change in the balance between excitation and inhibition may underlie this functional reorganization (27)(28)(29)(30)(31).…”
mentioning
confidence: 86%
“…Less is known about how the visual system remaps to cover the visual field after injury to area V1 or its input projection from the lateral geniculate nucleus (LGN). Enlarged receptive fields have been found in areas surrounding chronic V1 lesions in cats (20)(21)(22), and visual point spread functions were seen to enlarge over time in the areas surrounding focal V1 lesions in kittens (23). Smaller, shortterm changes (2 d after the lesion) have been reported as well (24).…”
mentioning
confidence: 93%
“…Such studies document the reorganization of cortical representations of the sensory inputs leading to the gradual filling-in of the cortical scotoma. 10 Other studies suggest that in the young brain some distant neurons are more vulnerable to the lesion, whereas others survive and expand their projections to bypass damaged and degenerated structures; the net result is sparing of neural processing and behaviours. 4 Others have suggested that interhemispheric connections are created in the presence of some striate cortex sparing.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The effects of early-acquired visual cortical lesions have been less extensively studied. [8][9][10] This is probably because in childhood, early-acquired lesions of the visual system are usually associated with extensive involvement of the retrochiasmatic visual pathways, leading to the wide spectrum of visual dysfunctions known as cerebral visual impairment (CVI), 11,12 whereas select ive injuries of the striate cortex are rare.…”
mentioning
confidence: 99%